A PROSPECTIVE SUTDY OF ETIOLOGICAL FACTORS IN NONDEFLATABLE FOLEY’S URETHRAL CATHETERS AND EVALUATION OF A DEFLATION TECHNIQUE - Mufti, Tariq; Sultan, Syed; Ahmed, Rashid; Nawaz, Mohammad; Qazi, Aziz Ahmed; Ali, Ghazanfar (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: A prospective study was conducted on 27 cases of non-deflatable selfretaining foley’s urethral catheters, comparing a number of variables like age, sex, disease, duration of catheterization, and type of catheter used. In addition, evaluation of a simple method of deflation of the balloons in stuck catheters carried out and the procedure is described. No definite conclusion is drawn as for the cause of obstruction to the balloon concerned. However, percutaneous suprapubic needle puncture without ultrasonic or radiographic assistance is found to be a safe, simple and effective technique for deflation of obstructed balloons of the catheters.